The future of physiological research: A greater understanding of female master athletes and aging? - Lorcan S. Daly (Physiological Reports)
Abstract High caliber master athletes provide a valuable model for studying inherent physiological aging and performance capacity, without the confounding factor of physical inactivity. Despite the remarkable achievements of female master athletes, their participation rates remain significantly lower than those of their male counterparts, particularly at more advanced ages. This review examines the biological sex gap in sports participation among master athletes and the subsequent disparity in empirical research, thereafter exploring possible contributing factors. It highlights the importance of studying female master athletes to better understand the aging process and offers recommendations to address current evidence gaps. The need for more comprehensive mechanistic data on highly trained older women, novel cataloguing and analysis of real‐world datasets, case studies/series, and longitudinal research are also emphasized. Although analyzing the records of female master athletes as a surrogate to determine age‐related physiological and performance changes is a common approach, the process may be hindered by the considerably lower participation rates of women. Therefore, an important step toward bridging these gaps is the longitudinal, integrative study of female athletes engaged in lifelong exercise. Such analyses would improve our understanding of senescence in women and may inform interventions targeting the promotion of physical function in older adults.